Analysis of Tuberculosis Risk Factors and Prevention Efforts in Coastal Areas of Indonesia : A Review - Hariati Lestari; Annisa Qoriyah Nur Ramadhany Suharsono; Nurinti (Journal of Health Science and Pharmacy, 2025)
Background: Tuberculosis (TB) continues to be a major global health concern, particularly in coastal regions where environmental conditions and limited public awareness increase the risk of transmission. Poor housing quality, overcrowding, and inadequate access to health information contribute significantly to the vulnerability of coastal populations. Objective: This study aims to identify the risk factors and prevention strategies for TB in coastal communities through a comprehensive review of the existing literature. Methods: A literature review was conducted by analyzing 20 relevant scientific articles obtained from credible databases. The selection of articles was based on predefined inclusion and exclusion criteria, focusing on studies related to TB in coastal settings. Results: The review highlights that environmental factors such as poor ventilation, high population density, and excessive indoor humidity significantly contribute to the prevalence of TB in coastal areas. Additionally, social and cultural misconceptions about TB, along with low adherence to treatment regimens, remain major barriers to effective disease control. Prevention strategies must include targeted health education, improved environmental sanitation, and active family involvement in supporting patient treatment. Conclusion: TB prevention in coastal communities requires an integrated and multidisciplinary approach that combines medical treatment, public education, and improvements in living conditions to reduce transmission and enhance treatment outcomes. Keywords: Sanitation, Risk Factors, Health Education, Tuberculosis, Coastal Communities, Indonesia.